The Application of Aversion Procedure Technique in Reducing the Frequency of Deviant Sexual Behavior in Students with Down Syndrome. (International Journal of Education and Literature, 2025)
This research was motivated by the condition of a subject who frequently displayed deviant sexual behaviors at school. The main objective of this study is to determine the effectiveness of the aversive procedure technique in reducing the frequency of sexual behavior deviations in a student with Down syndrome. The subject of this study was a tenth-grade student with Down syndrome at SKh Negeri 01 Kota Serang who exhibited deviant behaviors such as touching private parts of their body in public, hugging classmates without permission, and imitating sexual movements. The method used in this research was an experimental approach with a Single Subject Research (SSR) design of the A-B-A type, consisting of three phases: baseline-1 (A1), intervention (B), and baseline-2 (A2). The aversive procedure technique was applied by giving an unpleasant stimulus every time the deviant behavior appeared, aiming to create a deterrent effect and reduce the frequency of the behavior. The results of the study showed a significant decrease in the frequency of deviant sexual behavior after the intervention. This indicates that the aversive procedure technique is effective in reducing the frequency of deviant sexual behavior in students with down syndrome when implemented in a structured manner and adapted to the individual's psychological condition.